MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN METODE DEMONTRASI PADA PELAJARAN IPA TERPADU - Simatupang, Baharis Setia Adisahputra (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The objectives to be achieved in this study are: To find out whether there is an increase in student learning outcomes using the demonstration method in class VII-5 UPT SPF SMP Negeri 1 Sunggal, Deli Serdang Regency, for the 2019/2020 academic year. The research applies classroom action research methods using tests, observations, interviews, documentation and field notes. The research subjects were 32 students of class VII-5 UPT SPF SMP Negeri 1 Sunggal Deli Serdang Regency for the 2019/2020 academic year consisting of 16 male students and 16 female students. Giving demonstration methods to class VII-5 students at UPT SPF SMP Negeri 1 Sunggal for the 2019/2020 academic year can improve learning outcomes in Integrated Science subjects. This can be seen from the results of observations during learning activities by students, the results obtained from cycle I and cycle II are: 71% and 94%. In addition, the demo method can improve learning outcomes in Integrated Science subjects. The increase is evidenced by the results achieved from solving these questions well, based on the data and results of researchers, the results of filling out learning outcomes instruments on the subject of microscope and safety were obtained from 32 students, 7 completed while 25 people did not complete in cycle I and in cycle II, all 32 students completed.